PENDIDIKAN AGAMA ISLAM DALAM KEBUDAYAAN MASYARAKAT KALANG - Abdul Kholiq (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2015)
Kalang is one of sub-ethnic Javanese, that’s different to Java culturally. This study to explain about the function of islamic education as a cultural strategy for Kalang's society; and its adaptation its effect Islam values are entered. As cultural entity, Kalang's community build cultural identity based on cultural values inherited from ancestors. Kalang’s belief system has a theological religion historical ancient Javanese (Kapitayan). This belief bears the ritual Kalang as ‘gegalungan’, ‘ewuhan’ and ‘obong’. Through Islamic education, children’s of Kalang can recognize the values of Islam. Consequence of meets it cultural values that variably, there are three possibilities occur, as response of Kalang's person to that new values, which is first; the old value system won, or the new value system won, or third occurance of compromise.